NMDA receptors participate in the progression of diabetic kidney disease by decreasing Cdc42‐GTP activation in podocytes. Issue 2 (24th August 2016) - Shen, Jia; Wang, Rending; He, Zhechi; Huang, Hongfeng; He, Xuelin; Zhou, Jingyi; Yan, Yinggang; Shen, Shuijuan; Shao, Xue; Shen, Xiujin; Weng, Chunhua; Lin, Weiqiang; et al.
Abstract: Podocytes play important roles in the progression of diabetic kidney disease (DKD) and these roles are closely associated with cytoskeletal actin dynamics. N ‐Methyl‐d ‐aspartate receptors (NMDARs), which consist of two functional NR1 subunits and two regulatory NR2 subunits, are widely expressed in the brain but are also found in podocytes. Here, we found increased NR1 expression in two diabetic mouse models and in podocytes incubated in high glucose (HG). In diabetic mice, knockdown of NR1 using lentivirus carrying NR1‐shRNA ameliorated the pathological features associated with DKD, and reversed the decreased expression of synaptopodin and Wilms' tumour‐1. In podocytes incubated with HG, NR1 was secreted from the endoplasmic reticulum and this was blocked by bisindolylmaleimide I. NR1 knockdown decreased the cell shape remodelling, cell collapse, bovine serum albumin permeability, and migration induced by HG. After HG incubation, levels of cell division control protein 42 (Cdc42) and its active form increased, and a significantly higher Cdc42‐GTP level, increased Cdc42 translocation onto the leading edges, and lower migration ability were found in podocytes with NR1 knockdown. Increases in the number and length of filopodia were found in podocytes with NR1 knockdown but these were abolished by Cdc42‐GTP blockade with ML141. In conclusion, the activation of NMDARs plays an important role in DKD by reducing Cdc42‐GTP activation. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.